Implementasi Pembelajaran Inquiry Berbasis IT dalam Meningkatkan Semangat Belajar Pendidikan Agama Islam Siswa Kelas V SDIT Yabis Bontang Tahun Pelajaran - Rahman, Abd; Murni, Murni (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aims to explore and investigate the implementation of IT-based inquiry learning in enhancing the learning enthusiasm of Islamic Education for grade V students at SDIT Yabis Bontang during the academic year 2023/2024. The method used is qualitative with data collection through observation, interviews, and documentation. The subjects are students, and the results of the research show that the systematic application of IT-based inquiry learning by teachers creates a dynamic and interactive learning environment. The use of technology such as computers and projectors makes learning materials more interesting and easier for students to understand, which increases their activeness in asking questions, discussing, and collaborating. Observations and interviews revealed that students are more enthusiastic and frequently attend classes, and show improved academic results. Teachers reported that this method helps students understand religious concepts better and more relevantly. Overall, the implementation of IT-based inquiry learning has proven effective in enhancing learning enthusiasm and student engagement, creating varied and interesting learning, and improving their critical thinking skills.